Electrochemical characterization of nickel hydroxide nanomaterials as electrodes for NiMH batteries - Real, Silvia (2016)
β-Nickel hydroxide was successfully synthesized by a hydrothermal method. Nano-nickel hydroxide material was characterized by X-ray diffraction, infrared absorption spectroscopy, and transmission electron microscopy. They were employed as additives to the positive electrode of Ni-MH batteries. Working electrodes, with mixtures of commercial nickel hydroxide and nano-nickel hydroxide (0–10 wt.%) as active material, were prepared. Cyclic voltammetry, charge discharge profiles, and electrochemical impedance spectroscopy studies were carried out to evaluate the electrochemical performance of the nickel electrode, in 7 M KOH electrolyte, at 25 °C. The presence of nano-nickel hydroxide improves the electrochemical behavior of the active material. The electrochemical impedance spectroscopy (EIS) results were analyzed employing a modified version of previously developed physicochemical model that takes into account the main structural and physicochemical parameters that control these systems.